Pengembangan Kotak Dolananku Untuk Menanamkan Nilai-Nilai Pendidikan Karakter Gotong Royong Dan Kreatif Pada Anak - Iswantiningtyas, Veny; Wulansari, Widi; Khan, Rosa Imani; Pristiani, Yunita Dwi; Nursalim, Nursalim; Sofwina, Yolanda Titis (Efektor, 2023)
The life of the Indonesian people is very closely related to the character values of mutual cooperation and creativity. Instilling the values ​​of character education in children is of course very important, in this case the teacher as an educator who incidentally is in the school environment. In addition to having teaching duties, teachers also have an obligation to instill character education values ​​in children. Basically children learn through play, learning activities through play which are carried out to instill the values ​​of mutual cooperation and creative character education can use a game, namely My Dolanan Box. By playing My Dolananan Box, it can arouse children's interest and interest in learning.The purpose of this study was to produce a dolananku box game so that it can be used by Kindergarten teachers in learning activities that can instill the values ​​of mutual cooperation and creative character education in children. This research method uses the Borg & Gall development model. The results of this study are the product of the dolananku box game as a learning innovation to strengthen the value of the character of mutual cooperation and creativity. From the results of qualitative and quantitative descriptive analysis the results of the research show that: 1) My Dolanan box is suitable for use as a game to instill the values ​​of mutual cooperation and creative character education in children, 2) My Dolananan box can be used by the teacher as an efficient and interesting game to instill the values ​​of mutual cooperation and creative character education in children. For future researchers, it is expected to perfect the products produced both from media criteria, material content, playing activities. The results of this study in general can be concluded that the Dolananku box can be used by kindergarten teachers as a game to instill the values ​​of mutual cooperation and creative character education in children.